Interaction of dietary linoleic acid and α-linolenic acids with rs174547 in FADS1 gene on metabolic syndrome components among vegetarians - Ching, Yuan Kei; Chin, Yit Siew; Appukutty, Mahenderan; Ramachandran, Vasudevan; Yu, Choo Yee; Ang, Geik Yong; Gan, Wan Ying; Chan, Yoke Mun; Teh, Lay Kek; Salleh, Mohd Zaki (MDPI, 2019)
Fatty acid desaturase 1 (FADS1) gene controls the fatty acid metabolism pathway in the human body. The lower intake of α-linolenic acid (ALA) than linoleic acid (LA) among vegetarians may disrupt the fatty acid metabolism and limit the conversion of ALA to anti-inflammatory products such as eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA). This cross-sectional study aimed to determine the interaction of rs174547 in FADS1 gene with LA and ALA on metabolic syndrome (MetS) components. A total of 200 Chinese and Indian vegetarians in Kuala Lumpur and Selangor, Malaysia participated in the present study. The data on socio-demographic characteristics, vegetarianism practices, dietary practices, anthropometric measurements, blood pressure (BP), and overnight venous fasting blood samples were collected from the vegetarians. The rs174547 in FADS1 gene was significantly associated with MetS and its components such as waist circumference (WC) and fasting blood glucose (FBG). Multiple logistic regression analyses revealed that vegetarians with TT genotype of rs174547 in FADS1 gene had higher odds for MetS, larger WC, higher BP, and a lower level of HDL-c. Two-way ANOVA analysis showed that LA interacts with rs174547 in FADS1 gene to affect HDL-c (p < 0.05) among vegetarians. The present findings suggest the need to develop dietary guidelines for vegetarians in Malaysia. Prospective studies are also needed to affirm the interaction between LA and rs174547 in FADS1 gene on HDL-c among Malaysian vegetarians.